Detection of reactive oxygen species (ROS) generated by TiO₂(R), TiO₂(R/A) and TiO₂(A) under ultrasonic and solar light irradiation and application in degradation of organic dyes - Guo, Yuwei; Cheng, Chunping; Wang, Jun; Wang, Zhiqiu; Jin, Xudong; Li, Kai; Kang, Pingli; Gao, Jingqun (Journal of hazardous materials, 2011)
In the present work, the rutile, anatase and mixed (rutile and anatase) crystal phase TiO₂ powders were irradiated by ultrasound and solar light, respectively, and the generation of reactive oxygen species (ROS) were detected through the oxidation reaction from 1,5-diphenyl carbazide (DPCI) to 1,5-diphenyl carbazone (DPCO). The DPCO can be extracted by the mixed solvent of benzene and carbon tetrachloride and the extract liquors display an obvious absorption peak around 563nm. In addition, the influences of (ultrasonic or solar light) irradiation time, TiO₂ addition amount and DPCI concentration on the quantities of generated ROS were also reviewed. The kinds of generated ROS were determined by using several radical scavengers. At last, the researches on the sonocatalytic and photocatalytic degradation of several organic dyes were also performed. It is wished that this paper might offer some important subjects for broadening the applications of sonocatalytic and photocatalytic technologies.